Effects of Mg doping on electrical properties of Ba0.7Ca0.3TiO3 ceramics - Jaiban P. (2017)
© 2017 Elsevier Ltd (Ba 0.7 Ca 0.3 )Ti 1-x Mg x O 3-x ceramics where x = 0, 0.005, 0.015 and 0.02 were prepared employing a solid state sintering technique. The abrupt decrease of tetragonality was induced by doping with x ≥ 0.015. Ti K-edge X-ray Absorption Near-Edge Structure (XANES) spectra indicated spontaneous polarization weakness of doped ceramics. The grain size was decreased due to the creation of oxygen vacancies and solute-drag effect. The reduction of the phase transition temperature, ferroelectricity and piezoelectricity was observed in correlation with the decrease in tetragonality. Dielectric properties near room temperature of the samples could be enhanced with Mg addition. The results here suggested that the electrical properties of this ceramic may be largely tunable by Mg dopant and could be an attractive material for high-dielectric response devices.